Effects of temperature, light, and pH on the stability of fucoxanthin in an oil-in-water emulsion. (1st September 2019) - Zhao, Dong; Yu, Daeung; Kim, Moojoong; Gu, Ming-Yao; Kim, Sang-Min; Pan, Cheol-Ho; Kim, Gun-Hee; Chung, Donghwa
Highlights: Fucoxanthin degradation was much greater in o/w emulsion than in oil. The 9′- cis fucoxanthin was more stable than the other isomers except at pH 1.2. Fucoxanthin stability was the most significantly influenced by pH. Fucoxanthin stability was more influenced by temperature than by light. Total and all- trans fucoxanthin followed first-order degradation kinetics. Abstract: The effects of temperature, light, and pH on the stability of fucoxanthin in an oil-in-water emulsion were investigated with analyzing the kinetics and thermodynamics of fucoxanthin degradation. In the absence of light and air at pH 4.6, increasing the temperature from 25 to 60 °C significantly promoted fucoxanthin degradation. Total and all- trans fucoxanthin demonstrated an energetically unfavorable, non-spontaneous degradation with an Arrhenius temperature dependence. Increasing the light intensity up to 2000 lx at 25 °C and pH 4.6 caused a sharp degradation of total, all- trans, 13- cis, and 13′- cis fucoxanthin, but promoted the formation of the 9′- cis isomer. In the absence of light and air at 25 °C, decreasing the pH to 1.2 caused significant fucoxanthin degradation, whereas increasing the pH to 7.4 retarded the degradation. The property with the greatest influence on fucoxanthin stability was pH, followed by temperature and then light. Total and all- trans fucoxanthin followed first-order degradation kinetics.